Depot-medroxyprogesterone acetate: lipid profile changes and associated cardiovascular risks among recipients in Sagamu, South West Nigeria - Oluwaseyi Odelola; Adebay Akadri (AOSIS, 2023)
Depot-medroxyprogesterone acetate (DMPA) is a highly efficient form of long-acting reversible contraception. The use of DMPA has been linked to changes in lipid profile, although there is much controversy on the extent of these effects. Therefore, the objective of this investigation is to ascertain the impact of DMPA on the lipid profile and the corresponding cardiovascular hazards. Methods: This study was a forward-looking investigation carried out in the family planning clinic of Olabisi Onabanjo University Teaching Hospital Sagamu, Ogun State. A total of sixty-eight individuals who recently started using DMPA had their blood samples taken to assess their lipid profile at the beginning of DMPA use, as well as at 3 months and 6 months thereafter. The data were analyzed utilizing SPSS version 24. Results: After 3 months of using DMPA, there was a significant increase in the concentration of Total Cholesterol (TC) in the blood (p=0.022), as well as a significant increase in the concentration of Low Density Lipoprotein (LDL) (p=0.033). There was a non-significant increase in the concentration of Triglycerides (TG) (p=0.150) and a non-significant decrease in the concentration of Higher Density Lipoprotein (HDL) (p=0.076). Nevertheless, following 6 months of DMPA usage, there was a statistically significant rise in serum TC concentration (p=0.002), serum LDL concentration (p=0.003), serum TG concentration (p=0.001), and a substantial decline in serum HDL concentration (p=0.001). Conclusion: The use of DMPA is linked to elevated levels of blood TC, TG, and LDL, as well as a decrease in HDL after 6 months of treatment. These alterations in lipid profile may elevate the susceptibility to cardiovascular illnesses.